DEVELOPING STUDENTS’ ENDURANCE QUALITY IN PHYSICAL EDUCATION CLASSES (ON THE EXAMPLE OF GRADES 5-6) - Uraimov Sanjar; Ilyosova Maftuna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
This article provides information on developing students ’resilience to physical qualities and improving students’ physical fitness and thereby improving the quality of resilience in children. The degree of resistance to fatigue during exercise in muscle activity is called endurance quality.